The value of psychotherapy : the talking cure in an age of clinical science - Woolfolk, Robert L. (Guilford Press, 2015)
"Psychotherapy as a discipline is very much in flux. From a seasoned scholar, clinician, and teacher, this engaging book offers a thoughtful and current analysis of where the field is now and where it may be headed. Robert L. Woolfolk illustrates how the growing medicalization of mental health care--in particular, the attempt to fit psychotherapy to the templates of evidence-based medicine--have challenged psychotherapists to reaffirm the value of their work. The book explores ways in which certain kinds of efforts to endow "the talking cure" with greater scientific legitimacy can be problematic. Woolfolk makes a strong case for the benefits of psychotherapy not only as a technology for treating disorders, but also as a practice that can promote practical wisdom and human flourishing. Subject Areas/Key Words: biomedicine, CBT, client-centered, cognitive-behavioral therapy, evidence-based practice, growth, humanism, humanistic, iatrogenic, illness, manualized treatments, meaning, medicalization, mental health, person-centered, psychiatry, psychoanalysis, psychodynamic, psychopathology, psychotechnology, psychotherapists, psychotherapy, self-actualization, symptom Audience: Clinical psychologists, psychiatrists, clinical social workers, mental health and pastoral counselors, and psychiatric nurses; instructors and students in these fields. "--